The Impact of Motor Imageries on Aesthetic Judgment of Chinese Calligraphy: An fMRI Study - He, Mingcheng; Zhang, Wei; Shahid, Hira; Liu, Yushan; Liang, Xiaoling; Duan, Yan; Wang, Hua; He, Xianyou (Frontiers in Human Neuroscience, 2021)
Previous behavioral studies on aesthetics demonstrated that there was a close association between perceived action and aesthetic appreciation. However, few studies explored whether motor imagery would influence aesthetic experience and its neural substrates. In the current study, Chinese calligraphy was used as the stimuli to explore the relationship between motor imagery and the participant’s aesthetic judgments through functional magnetic resonance imaging (fMRI). Imaging results showed that, compared with the baseline, the activation of the brain regions involved in perceptual processing, cognitive judgments, aesthetic emotional, and reward processing were observed (e.g., anterior cingulate cortex, putamen, and insula) after the participants performed motor imagery tasks. The contrast analyses within aesthetic judgments showed that kinesthetic imagery significantly activated the middle frontal gyrus, postcentral gyrus, anterior cingulate cortex, and thalamus. Generally, these areas were considered to be closely related to positive aesthetic experience, and suggested that motor imagery, especially kinesthetic imagery, might be specifically associated with the aesthetic appreciation of Chinese calligraphy.